Kopi Jahe Merah Khas Sumenep Madura di Desa Mulyoagung Jetis Kabupaten Malang - Nuriyanti, Ika; Suhermin Ingsih, Ita; Nikin Hardati, Ratna (Jurnal Pemberdayaan Masyarakat, 2021)
Home industry in Mulyoagung Village, Dukuh Jetis, Dau District, Malang Regency is engaged in micro business, namely The Making of Red Ginger Coffee. IRT "Yuli" has several problems, including: Red Ginger coffee production equipment is still simple, equipment has not been touched by science and technology, production results are not optimal, coffee sales income is not optimal, there is still a lack of understanding of hygienic and quality ginger coffee. There is a good seal and plastic to package the product, and there is also no proper economic analysis (marketing management) that is able to support the sale of ginger coffee products. Through this PKM, existing problems will be resolved by: Designing and making a ginger coffee grinder. Making a stamp tool for the ginger coffee brand. Providing training on bookkeeping and financial administration through POAC (Planning Organizing Actuating Controlling) concept. Providing training and mentoring to partners for hygienic ginger coffee making. The output targets are: 1) Manifesting a ginger coffee grinder tool so as to produce hygienic and clean ginger coffee; 2) Manifest the ginger coffee stamp as a packaging attraction for sales; 3) Providing training on management arrangements; and 4) Providing training for hygienic ginger coffee making.